Peculitaries of carbohydrate metabolism in patients with metabolic syndrome depending on C/Т polymоrphism in the DIO 1 gene - N. O. Abramova; N. V. Pashkovska (Patologìâ)
According to the WHO, the prevalence of metabolic syndrome (MS) is 20–40 %. Thyroid hormones are involved in the regulation of almost all physiological processes in the body, including carbohydrate metabolism.